شهيد الجبل الأزرق مصطفى بن بوالعيد 1916-1956 - جبلي, الطاهر (جامعة الوادي - University of Eloued, 2018)
Abstract Martyr of the Blue Mountain Mustapha Ben Boulaid(1917 /1956) The revolution of November 1 st , 1954 was associated with the brightest leaders who were known by their rare courageous which was built up from their high morals and qualities .Their political and military genius was appeared , challenging all the colonial obstacles and plans which were created by the enemy to crush the revolution . The most distinguished Man , Mostapha Ben Boulaid was one of the nationalist pioneers and activists who believed in the futility of the political fight and one of the few formers who led the revolutionary project and mixed the papers in Matignon .He was that Man who divided his short life equally between the prison and the mountain. The Occasion, then, is just for remembrance and a reminder of the powerful and strength elements and virtues of that Man who has done his best and has given his life and his personal wealth to serve the revolution for the sake of Algerian’s revival at a time when there was no signs of nearer political or military victory. In this study, we will attempt to monitor the biography and the journey of the hero mustapha Ben Boulaid ,from his birth till his death on March 22nd,1956 and also through prominent stations of his struggle life in Algerian ‘s people party , victory movement for democratic freedoms ,and his position from the massacres of May 8th,1945. Then, his efforts in special organization, particularly in Aouras . In addition to this,his pioneer and distinguished role to prepare for the outbreak of the liberation revolution in November, 1st 1954. The colonial writings also, confess that the liberation revolution in its first stage was the efforts of Ben Boulaid in vew of his role in structuring the revolution, collecting weapons and in organizing network of logistical help in Northern borders . The end of the hero in this Epic was a surprise as he was martyred on March ,22 nd 1956 in a difficult circumstances which faced the revolution in its first stage.
مقال
Keywords: مصطفى بن بولعيد، الثورة الجزائرية، الجبل الأزرق